EFEKTIVITAS MODEL INKUIRI BERBANTUAN MODUL DALAM MENINGKATKAN PEMAHAMAN KONSEP DAN KETERAMPILAN GENERIK SAINS (Universitas Negeri Semarang, 2014)
Student-centered learning paradigm requires teachers to reduce the dominance of the teacher in the learning activities so students can optimally develop their potentials, such as generic science skills. This study aims to determine the effectiveness of the application of the Inquiry Based Learning (IBL) assisted module to an improved concepts understanding and generic skills of students of senior high school in Ngawen in the buffer material and salt hydrolysis. The population was all students in class XI IPA of that senior high school in 2012/2013 academic year. The research design is a pretest and posttest group design. Sampling technique used is cluster random sampling, derived class XI IPA 1 as experimental class and class XI IPA 2 as the control class. The results showed that the average posttest’s score of concept understanding of experimental class 84,00 and control class 77.52. In the experimental class obtained the clasical completeness 97% and control class 83%. The result of first and second lab observation obtained the average score of generic science skill at the experimantal class were 83,43 and 93,51 while the control class were 81.41 and 91.59. Based on the results of this study, it can be concluded that implementation of the IBL model through module was effective in improving the understanding of science concepts and generic skills of students.Keywords: Generic Science Skills, Inquiry Guided Module